Implementation Of E-Government New Normal Innovation Online Campus Research Information System (Neni Si Linca) At The Investment And One-Door Integrated Services Office Of South Sulawesi Province - ningsih, nining_angraeni; Andi Aslinda; Suarlin; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2025)
This study examines the implementation of E-government through the New Normal Online Campus Research Information System (NENI SILINCA) at the Investment and Integrated One-Stop Service Office (DPMPTSP) of South Sulawesi Province. It aims to identify both the supporting and inhibiting factors affecting the system's role in enhancing the efficiency, transparency, and accessibility of public services. The study adopts a descriptive qualitative approach, employing data collection methods such as observation, interviews, and documentation. Data were analyzed through the processes of data condensation, data display, conclusion drawing, and verification. The findings indicate that the implementation of NENI SILINCA has contributed positively to public service delivery. The system enables students to process research permit applications online, thereby streamlining administrative procedures and reducing operational costs. Transparency is significantly improved, as users can monitor the progress of their applications in real-time. From the policy content perspective, NENI SILINCA promotes digital transformation in public services by providing faster and more convenient access. Nonetheless, several technical obstacles remain, including system errors, unstable internet connectivity, and ambiguity in document requirements for students conducting research outside their home region. From the implementation context perspective, the success of this initiative is influenced by political commitment and institutional capacity. The leadership of the Governor and the Head of DPMPTSP plays a pivotal role in ensuring the system’s effectiveness. Cross-sector collaboration with educational institutions and technical teams also facilitates clearer task division and coordination. Key enabling factors include strong regulatory support, the technical team’s readiness, and policy socialization efforts. However, limitations such as inadequate outreach and frequent network disruptions continue to pose challenges. Therefore, enhancing technological infrastructure and adopting more effective communication strategies are essential to ensure the optimal and sustainable implementation of NENI SILINCA as a digital innovation in public service.